ENHANCING EARLY CHILDHOOD LEARNING EXPERIENCE WITH AUGMENTED REALITY MODELING OF ANIMALS AND DEEP LEARNING - Ghanis Putra Widhanarto; Seftia Kusumawardani; Titi Prihatin; Anang Kabul Prastyo (Akademika, 2023)
The pandemic condition greatly influences the educational sector where the learning process must be carried out online which causes the learning experience of children to become less. Education in early childhood is developed to provide meaningful and enjoyable real experiences for children. AR technology is a new digital innovation where many experiences can be obtained without bringing the actual conditions. The objectives of this study are to Analyze the needs for technology-based learning models at the early childhood education level in Indonesia; and Develop mobile-based AR technology using deep learning to improve early childhood learning performance in the present time. The research began with a needs analysis, followed by the development of AR products, then limited trials were conducted and trials on respondents, namely early childhood. The results of the research show that the deep learning-based AR technology developed has a positive effect on improving early childhood learning performance in mastering animal introduction materials. This study has implications for the learning process and in the long run provides benefits to the wealth of applied educational technology science.